2013
DOI: 10.15218/zjms.2013.0026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of primary schools' environment in Erbil city

Abstract: Background and objective: Healthy school environment is one of the main determinants of students' health in order to maximize the benefit from the educational programs. This study was aimed to assess the primary school environment in Erbil city. Methods: A cross-sectional study was conducted in 50 primary schools in Erbil city out of 242 schools through the academic year 2010-2011. Data were collected using a questionnaire constructed by the researchers which included general information, area around the schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…About 73% of the students who were exposed to wounds during school time did not receive the initial treatment for wounds such as sterilization or putting on gauze, and this is completely consistent with a previous study that indicated the same problem where some students had to return to their homes to seek treatment which means that their wounds remain for several hours, exposed to bacterial contamination (20) . The issue goes beyond poor sanitation and school environment, as some schools lack first aid materials (21) and even if they are available, it has been found that educational personnel are not trained or lack primary medical information and have not been engaged in training courses on how to do first aid (22) . The results of the cultural properties showed that about a quarter of the students 24% of the students were MRSA carriers.…”
Section: Discussionmentioning
confidence: 99%
“…About 73% of the students who were exposed to wounds during school time did not receive the initial treatment for wounds such as sterilization or putting on gauze, and this is completely consistent with a previous study that indicated the same problem where some students had to return to their homes to seek treatment which means that their wounds remain for several hours, exposed to bacterial contamination (20) . The issue goes beyond poor sanitation and school environment, as some schools lack first aid materials (21) and even if they are available, it has been found that educational personnel are not trained or lack primary medical information and have not been engaged in training courses on how to do first aid (22) . The results of the cultural properties showed that about a quarter of the students 24% of the students were MRSA carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Abdulla, Najib [13] presented a survey covered 50 primary schools in Erbil city out of 242 schools covered the educational year 2010-2011. The informations were collected using a survey made by the scholars who included general evidence, the area nearby the school, school environment.…”
Section: Literature Reviewmentioning
confidence: 99%